(Learning Media Development) Flipbook Cake Decoration Ornaments Made of Fondant For Deaf Students at SLB Negeri 01 Jakarta) - Adhwa, Daffa Syifa Amadea; Artanti, Guspri Devi; Cahyana, Cucu (JUPE : Jurnal Pendidikan Mandala, 2025)
This research aims to develop a learning media, a flipbook,  of cake decoration ornaments made from fondant for Deaf students at SLB Negeri 01 Jakarta. The method used in this research is Research and Deveplopment (R&D) with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The results showed that the learning media developed had been validated by 2 SLB teachers who were material experts in the culinary area, language area and media with good qualifications. The development of learning media is stated through the results of validation to media experts, which produces a percentage of 84%, for material experts in the culinary area the resulting percentage is 97.5% and the test results obtained from linguistics are 74.5%. The trial to Deaf students showed positive results, with a feasibility percentage of 75.9% in the one-to-one trial and 77.7% in the small group trial. The results of this research can be concluded that this flipbook media is expected to improve the understanding and skills of Deaf students in cake decoration, as well as make a positive contribution to inclusive education.